A novel approach to improve quality of service in MANET using cache update scheme for on-demand protocol. (2017) - Mandhare, V.V.; Thool, V.R.; Manthalkar, R.R.
The route cache scheme used by on-demand routing protocol is significant in MANET. This paper presents, new cache update algorithm which determine broken link information to all neighbour's that can cache the route in routing table using distributed cache update algorithm in first stage. Then new time-to-live (TTL) field is attached with every cache entry to remove when it is expired at second stage. The proposed cache updated scheme not only maintains cache structure but also stores the information required for cache update. The proposed cache update scheme has been experimentally evaluated using network simulation (NS2). The analysis shows improved performance of updated dynamic source routing (UDSR) protocol up to 60% to 70% in terms of QoS parameters like packet delivery ratio, delay, routing overhead, drop rate compared to conventional dynamic source routing (DSR) protocol and 30% to 40% improvement compared to method presented in literature.